Impact of Different Fine Aggregates on the Compressive Strength of Hollow Sandcrete Blocks - Odeyemi, S.O.; Abdulwahab, R.; Anifowose, M. A.; Ibrahim, R. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Sandcrete blocks are walling materials that are made of fine aggregates and cement. Though, sandcrete blocks are being used as building materials in many parts of Nigeria, it has been discovered that many of the blocks produced do not conform to the minimum compressive strength requirement for such blocks. This study, therefore, examined the effect of using four (4) different fine aggregates (quarry dust, river sand, shocking sand and plastering sand) with binder to aggregate mix ratios of 1:6 and 1:4 on the compressive strength of sandcrete blocks. Specific gravity and particle size distribution analyses were conducted on the fine aggregates to determine their properties while water absorption capacity and compressive strength tests were carried out on the hollow sandcrete blocks. Five samples from each aggregate of size 450 mm x 225 mm x 225 mm were moulded and subjected to compressive strength tests. The water absorption capacity results revealed that shocking sand has the highest capacity to absorb water with a value of 8.69 %. River sand, with a value of 6.67 % has the lowest water absorption capacity. The 28th day compressive strength test results of 1.31 N/mm2, 1.10 N/mm2, 0.78 N/mm2 and 0.50 N/mm2 for the sandcrete blocks produced from quarry dust, river sand, shocking sand and plastering sand respectively, with mix ratio 1:6, did not meet the minimum requirement of 2.5 N/mm2 specified by NIS 87:2007 for non-load bearing walls. However, with mix ratio of 1:4, the compressive strength of 2.52 N/mm2 and 2.50 N/mm2 for sandcrete blocks made with quarry dust and river sand respectively met this minimum requirement. It was concluded that only quarry dust and sharp sand at mix ratio 1:4 are suitable in the production of sandcrete blocks.